Morphological and phylogenetic diversity of Pythium and related genera (Pythiaceae, Pythiales) from some areas in eastern Thailand - Rattasit Saelee; Kanungnid Busarakam; Prommart Koohakan; M Ali-Shtayeh; A Saleh; N Allain-Boul; C Lvesque; C Martinez; R Blanger; R Tweddell; R Bennett; B Nam; et al. (Agriculture and Natural Resources, 2022)
Importance of the work: Pythium and related genera in the class Oomycetes are an important microorganism group that affects environmental stability due to their diverse lifestyle patterns. However, full information on their distribution is limited in Thailand. Objectives: To describe their oomycetes distribution in Chanthaburi, Rayong, and Trat provinces, eastern Thailand and provide their diversity and phylogenetic data. Materials & Methods: Composite soils samples were collected July-September 2019. Three techniques (soil baiting, soil dilution and soil plating) were used for isolation. Isolated oomycetes species were obtained from different locations (mangrove forest, natural forest, cultivated field and a river). The isolates were characterized using combined data of morphological traits and sequences analysis of the internal transcribed spacer region (ITS). Results: In total, 52 oomycetes were isolated and assigned to 11 species (Globisporangium carolinianum, Globisporangium splendens, Pythium acanthicum, Pythium deliense, Pythium diclinum, Pythium longipapillum, Pythium myriotylum, Pythium torulosum, Phytopythium cucurbitacearum, Phytopythium helicoides and Phytopythium vexans). Phylogenetic trees of the ITS region analysis indicated that the species obtained from the various locations in this investigation shared a similar biological trait of Pythium and related genera within clades A, B, D, I and K. Main finding: This was the first report of P. longipapillum recovery in Thailand and perhaps the first publication of this species in Thailand and Southeast Asia. Identification and descriptions of Pythium and related genera were provided, as well as useful information to understand their distribution in Thailand's unique ecosystem.
Keywords: Plant Pathogens and Resistance